Evidence for the Involvement of Gene Regulation of Inflammatory Molecules in the Accumulation of Intracellular Cholesterol: The Mechanism of Foam Cell Formation in Atherosclerosis - Sukhorukov, Vasily Nikolaevich; Khotina, Victoria Alexandrovna; Borodko, Daria Dmitryevna; Ekta, Mariam Bagheri; Oishi, Yumiko; Omelchenko, Andrey Vladimirovich; Kolmychkova, Kira Ivanovna; Nikiforov, Nikita G.; Sobenin, Igor Alexandrovich; Orekhov, Alexander Nikolaevich (Current Medicinal Chemistry, 2025)
BackgroundThe relationship between the cellular pro-inflammatory response and intracellular lipid accumulation in atherosclerosis is not sufficiently studied. Transcriptomic analysis is one way to establish such a relationship. Previously, we identified 10 potential key genes (IL-15, CXCL8, PERK, IL-7, IL-7R, DUSP1, TIGIT, F2RL1, TSPYL2, and ANXA1) involved in cholesterol accumulation in macrophages. It should be noted that all these genes do not directly participate in cholesterol metabolism, but encode molecules related to inflammation.MethodsIn this study, we conducted a knock-down of the 10 identified key genes using siRNA to determine their possible role in cholesterol accumulation in macrophages. To assess cholesterol accumulation, human monocyte-derived macrophages (MDM) were incubated with atherogenic LDL from patients with atherosclerosis. Cholesterol content was assessed by the enzymatic method. Differentially expressed genes were identified with DESeq2 analysis. Master genes were determined by the functional analysis.ResultsWe found that only 5 out of 10 genes (IL-15, PERK, IL-7, IL-7R, ANXA1) can affect intracellular lipid accumulation. Knock-down of the IL-15, PERK, and ANXA1 genes prevented lipid accumulation, while knock-down of the IL-7 and IL-7R genes led to increased intracellular lipid accumulation during incubation of MDM with atherogenic LDL. Seventeen overexpressed genes and 189 underexpressed genes were obtained in the DGE analysis, which allowed us to discover 20 upregulated and 86 downregulated metabolic pathways, a number of which are associated with chronic inflammation and insulin signaling. We also elucidated 13 master regulators of cholesterol accumulation that are immune response-associated genes.ConclusionThus, it was discovered that 5 inflammation-related master regulators may be involved in lipid accumulation in macrophages. Therefore, the pro-inflammatory response of macrophages may trigger foam cell formation rather than the other way around, where intracellular lipid accumulation causes an inflammatory response, as previously assumed.
Keywords: macrophages